Everyday Auditory Environment Among Elderly Cochlear Implant Users. - Larsson, Ulrika; Löfkvist, Ulrika; Hallin, Karin (Audiology Research, 2025)
Background/Objectives: For most adults receiving a cochlear implant (CI), the primary goal is to enhance their oral communication with others. The aim of this study was to investigate the total CI usage time per day among retired CI users and to characterize in which auditory environments they were using their CI. One additional aim was to analyze whether usage time, auditory environment, or social factors influenced CI speech perception. Methods: Participants completed a questionnaire addressing retirement status, whether they lived with another adult, educational level, and participation in social activities. Speech perception scores were obtained from medical records, and CI datalogging was extracted from the CI programming software. Results: Seventy-three CI users aged >65 years were included. The average usage was 12.9 h/day. No statistically significant correlations were found between total usage time or time spent listening to speech and CI speech perception. CI users who regularly met with family or friends had statistically significantly higher CI speech perception than those who did not (p = 0.003). Conclusions: Social interaction may play a crucial role in supporting speech perception among elderly CI users. Opportunities for communication and participation in social life appear to be important for maximizing benefit.